Modified tibial tuberosity advancement procedure with tuberosity advancement in excess of 12 mm in four large breed dogs with cranial cruciate ligament-deficient joints - Burns, C. G.; Boudrieau, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Objective: To describe a modification of the tibial tuberosity advancement (TTA) procedure that required tuberosity advancement in excess of 12 mm for the stabilization of cranial cruciate ligament (CrCL) deficient stifle joints. Methods: Four large breed dogs with CrCL deficient stifle joints (one bilateral) underwent a modified TTA of 15 or 16 mm in order to obtain a patellar tendon angle of 90° to the tibial plateau slope or common tangent between femur and tibia in the extended limb position. The desired TTA was achieved by displacing a 12-mm cage distally; this displacement distance was calculated from two similar triangles formed within the planned osteotomy site. An allogenous cancellous bone block placed proximal to the cage provided buttress support; a corticocancellous allograft filled the remainder of the gap. Tibial tuberosity fixation was performed as previously described. Results: Healing of the osteotomy defects with incorporation of the cancellous block was observed at a mean of 8.6 weeks postoperatively. Normal return of limb function was reported in all of the dogs except for one dog that underwent revision surgery four months postoperatively for a continued lameness. Technical errors at the time of the original surgical procedure in this dog resulted in insufficient tuberosity advancement; additional advancement was performed, which resolved the lameness. Clinical significance: Results in this series suggest that our modification of the TTA, in order to advance the tuberosity in excess of 12 mm, could be successfully obtained using the currently available implants.
Keywords: Cranial cruciate ligament; tibial tuberosity advancement; TTA; stifle joint; dog